THE EFFECT OF LOCAL GOVERNMENT POLICIES AND SERVICES ON THE EMPOWERMENT OF CATTLE FARMERS IN SRAGEN - Bayuseno, Tri Agus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
Good service from the government to the community must be realized with the existence of policies that are impartial and beneficial for all members of the community (in this case cattle farmers). Therefore, the policies issued and the services provided by the government especially the regional government are expected to have a significant influence on community empowerment in the region. With this, the author tries to examine the effect of the policies and / or services of the Regional Government on the empowerment of cattle farmers in Sragen Regency, Central Java. It is expected that the policies and / or services of the local government have a good influence on the empowerment of cattle farmers in this area and can be applied in other areas. The methodology used in this study combines several data collection and analysis techniques. In general, this study uses explanatory methods that describe, describe and explain until reaching the conclusion of the answer to each problem we examine. The results of this study are expected to be the first step of further research to jointly make the relationship between the serving government and the community more and better. Keywords: Policy, Services, Local Government, Empowerment, Cattle Breeders